KAJIAN EMPIRIS DETERMINAN AKTIVA PAJAK TANGGUHAN (Students' Journal of Accounting and Banking, 2012)
This study aims to analyze: the factors that may be considered or influence (predictor) on the balance of deferred tax assets. With this test are expected to obtain empirical evidence that a variable determinant of the deferred tax asset as the implementation of SFAS No. 46 on Accounting for Income Taxes.The population of this study is manufacturing companies listed on the Indonesia Stock Exchange in the year 2006-2010. There are 19 companies that could be used as study sample. Sample selection is done by purposive sampling method.The results showed that the independent variable (the future reversal of existing taxable temporary differences, tax strategy, operating income, cash flow, loss carryforward from temporary differences, other post employment benefits and market value) jointly affect the amount of deferred tax assets. However, only individual variables from temporary differences and the market value loss carryforward is positive and significant effect on the amount of deferred tax assets. Variable the future reversal of existing taxable temporary differences, tax strategy, operating income, cash flow and other post employment benefits not significantly affect the amount of deferred tax assets.Keywords: deferred tax assets, the future reversal of existing taxable temporary differences, tax strategy, operating income, cash flow, loss carryforward from temporary differences, other post employment benefits, the market value.